Distribution of pathogenic and opportunistic microorganisms in raw materials and products of animal origin - I. O. Chemerovska; I. O. Rublenko; I. V. Musiets; O. I. Horbatyuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Among scientists and specialists of veterinary medicine, there is concern about the further growth of infection with Escherichia coli bacteria and bacteria of the genera Staphylococcus and Proteus. The purpose of our research was to investigate the distribution of pathogenic microorganisms Escherichia coli and bacteria of the genera Staphylococcus and Proteus in raw materials and products of animal origin on the territory of Ukraine for the period 2020–2023. The study was conducted at the Department of Microbiology and Virology of the Bila Tserkva National Agrarian University (BNAU), Bila Tserkva, and at the Research Bacteriological Department of the State Research Institute for Laboratory Diagnostics and Veterinary Sanitary Examination (DNDILDVSE), Kyiv. Results of microbiological monitoring of non-compliance with microbiological criteria for the detection of Escherichia coli and bacteria of the genera Staphylococcus and Proteus (for the period 2020–2023) showed that the highest percentage of bacteria of the genus Staphylococcus spp. was found in 2023 when testing samples of meat, minced meat, milk, dairy products, and fish, with the smallest number of samples tested, compared to the results of studies in other years. The largest number of Escherichia coli isolates was detected in water and candy samples in 2020, in vegetable samples in 2021. In 2020, 2 Escherichia coli isolates and 0.13 % of Staphylococcus bacteria were isolated in the study of semi-finished products from pork meat and Proteus for 1509 samples examined. In 2021, out of 1259 samples, 3 (0.23 % of those tested) positive results were found; in 2023 – one (0.10 % of those surveyed). Data analysis shows that during the experimental period, the largest number of bacterial isolates of Proteus spp. was isolated in 2021. No bacteria of the genus Proteus were detected during tests for compliance with microbiological criteria of samples of fish (n = 348), water (n = 2240), vegetables (n = 137) and sweets (n = 207). When testing water samples, the contamination was 1.27 % of the 1179 samples tested. In 2021, 1,436 samples were examined, of which 7 were found to be positive (0.48 % of those examined). During the testing of candy samples (n = 33) in 2020, 1 isolate of Proteus spp. Thus, according to the results of the tests for compliance with the microbiological criteria for pathogenic agents for the period 2020–2023. the presence of pathogenic bacteria Escherichia coli, Proteus spp., and Staphylococcus spp. was established. in raw materials and products of animal origin, which indicates a danger to humans and their spread among animals and birds.